Investigation on the grain size effect on the copper shaped charge jet stretching behavior - Jiang, Yao; Gu, Rui Cong; Wang, Jing Tao; Xiao, Qiang-Qiang; Huang, Zheng-Xiang (Frontiers in Materials, 2022)
The grain size effect on the shaped charge jet (SCJ) stretching process was analytically formulated and experimentally verified by penetration tests. The present analytical model predicts an optimum grain size for the SCJ performance, deduced from the concurrent effect of grain size on flow stress, strain rate sensitivity, and surface roughness. Specifically, reducing the grain size will improve the initial surface roughness and decrease the initial perturbation amplitude, favoring the SCJ stretching. On the other hand, the strain rate sensitivity and flow stress for copper increases with the decrease of grain size, facilitating the perturbation growth and leading to a premature breakup. Thus, the present analytical model predicates the optimum grain size of the SCJ is about 1~5 μm. The penetration test verified that the shaped charge liner with an average grain size of about 3.6±2.5 μm exhibited the largest penetration depth. The consistent result from the analytical model and penetration experiments certifies the feasibility of the present analytical model on the SCJ performance.